2019
DOI: 10.1159/000505599
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HPV Genotypes in Adult Male Patients with Cutaneous Warts: A Cross-Sectional Study

Abstract: Significance of the Study • Nine human papillomavirus (HPV) types were detected in body warts taken from adult male patients. • Five were from the α genus (HPV2, 6, 27b, 57b, 57c, and 94), 2 from the γ genus (HPV4 and 65), and HPV1a was from the mu genus. • Single HPV infection was found in 93.4% of the patients (HPV27b was the most common type), whereas multiple infections were encountered in 6.6% (HPV1a was the most common type, followed by HPV27b).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 16 publications
0
17
2
Order By: Relevance
“…As regards to the application of the test on a cohort of FFPE wart biopsies, multiple HPV infections were detected in 35% (95% CI: 21%–52%) of biopsies. This is in contrast to the current literature claiming that in immunocompetent patients only 4%–16% of cutaneous warts exhibit multiple HPV infections 4,10,17–19 . The observed occurrence of multiple infections is probably due to the high sensitivity of the newly developed HPV qPCR assay.…”
Section: Resultscontrasting
confidence: 87%
“…As regards to the application of the test on a cohort of FFPE wart biopsies, multiple HPV infections were detected in 35% (95% CI: 21%–52%) of biopsies. This is in contrast to the current literature claiming that in immunocompetent patients only 4%–16% of cutaneous warts exhibit multiple HPV infections 4,10,17–19 . The observed occurrence of multiple infections is probably due to the high sensitivity of the newly developed HPV qPCR assay.…”
Section: Resultscontrasting
confidence: 87%
“…Interestingly, after bivariate and multivariate analysis, only three factors remained statistically associated with HR-HPV in our study population: a young age (< 41 years), multiple sex partners (> 3), and the consumption of tobacco. As previously discussed, young women stand a higher risk of HR-HPV in several RLS, which is also partly due to the immaturity of the cervix during adolescence, as many among them engage in sex at early age ( Al-Awadhi et al., 2019 ; Beyazit et al., 2018 ; Gravitt et al., 2007 ; Prakash et al., 2016 ; Sellors et al., 2000 ). Furthermore, several studies have shown a significant increase in HR-HPV among women having sex with multiple partners ( Castellsagué and Muñoz, 2003 ; Hernandez et al., 2008 ; Sellors et al., 2000 ).…”
Section: Discussionmentioning
confidence: 92%
“…in Nigeria ( Atashili et al., 2012 ; Sosso et al., 2020 ), the most represented age group in our study population (median age 41 years) was 30–39 years. This observation may be supported by the fact that young people (aged 19–39 years) are predominant in Cameroon and SSA in general, are more at risk of a surge in HR-HPV ( Al-Awadhi et al., 2019 ; Sellors et al., 2000 ), and account for more than 50% of infections worldwide ( Beyazit et al., 2018 ; Gravitt et al., 2007 ; Prakash et al., 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…8 One of the most distinctive features of the papillomavirus group is its host-specific genotypic restriction, and the preference of certain types of papillomavirus for different anatomical sites. 2 With technological advances, it has been possible to identify at least 150 genotypes of the HPV virus. 9 The common wart is more closely associated with HPV types 1, 2, 4, 7, 27 and 57.…”
Section: Discussionmentioning
confidence: 99%
“…1 Transmission of the common wart virus can occur directly (autoinoculation) or indirectly through environmental exposure, which can happen on beaches, at sports venues, swimming pools, and other locations. 2 Physical activity, despite conferring numerous benefits to human health, can cause the development of infectious or inflammatory dermatoses due to direct contact through the skin or with shared materials, and excessive sweating. 3,4 The impairment of the skin barrier favors the transmission of viral, bacterial and fungal diseases.…”
Section: Introductionmentioning
confidence: 99%